Analisis Karakteristik Kemasan Teh Angry Birds Terhadap Keputusan Pembelian Konsumen (Studi pada STIE Mahardhika Surabaya) - Sofyan Lazuardi (UNUSA Press, 2016)
This study aimed to analyze the influence of the characteristics of the Angry Birds packaging (packaging size, packaging, color packaging, packaging materials) partially have a significant influence on consumer purchasing decisions (STIE Mahardhika case study in Surabaya). The analysis model used is the t test regression analysis to see the effect of the variable characteristics of the packaging (packaging size, packaging, color packaging, packaging materials) on consumer purchasing decisions. This study was conducted in STIE Mahardhika Surabaya. Samples taken are students STIE Mahardhika Surabaya totaling 100 people. The analysis technique used is multiple linear regression using SPSS. Based on t test known that the size of the packaging and the packaging forms a partial no significant influence on purchase decisions Mahardhika STIE student. The different thing is indicated by the color variables packaging and packaging materials, both variables have a significant influence on purchasing decisions.